The administration of unclaimed estates in West Malaysia : formulating a legal framework - Rahmawati binti Mohd Yusoff (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
Issues relating to the unclaimed estates are crucial, as it had been reported that there are more than a million cases of unclaimed estates since 2006. In 2016, it was reported that the latest value of the unclaimed estates in West Malaysia stands at RM60 billion. However, the exact types and actual value of unclaimed estates remain questionable and not specifically identified in any research, specific data or findings. In pursuant thereto, this research analyses the exact types and values of the unclaimed estates as well as the issues, factors and impacts of the unclaimed estates based on the qualitative and descriptive cross-sectional analysis through the governing statutes, reported cases, the semi-conducted interviews, surveys, and data obtained from the respective administrative bodies. The issues are also examined from the Islamic perspective based on Qur'an, Sunnah, and views of Muslim jurists. For the comparative analysis, the research also provides the reference of the system for the administration of unclaimed estates in Singapore and the United Kingdom. The research finds that there are four categories of unclaimed estates namely, the unclaimed money that is put under the custody of the Registrar of the Unclaimed Moneys, undistributed funds that is held on trust by the Public Trust Corporation, non-administered estates whereby no application has been initiated by the beneficiaries for estates distribution and the case of bona vacantia whereby personal estate of the non-Muslim's accrues to the Government and the real estate reverts to the State Authority, with the exception to the rights of Baitulmāl in the deceased Muslim's estate. Out of these four types of unclaimed estates, there is only one category that is left frozen which is the non-administered estates due to lack of ownership in the management of such estates. The research also discovers that the available system and mechanism in Malaysia are not accommodating in tracing the beneficiaries if there is no application to administer the estate. Hence, reforming the existing legal and procedural frameworks for the administration of the non-administered estates is highly necessary in order to manage the current situation and to prevent future non-administered estates from recurring.